Gravimetry through non-linear optomechanics - Sofia Qvarfort (Nature Portfolio, 2018)
Precise gravimetric measurements are an important but challenging task. Here, Qvarfort et al. theoretically show that, in an optomechanical cavity, only the phase of the optical output needs to be measured to obtain a precise value for the gravitational acceleration with high sensitivity.